X-ray diffraction from shocked crystals: Experiments and predictions of molecular dynamics simulations - Rosolankova, K; Kalantar, D; Belak, J; Bringa, E; Caturla, M; Hawreliak, J; Holian, B; Kadau, K; Lomdahl, P; Germann, T; Ravelo, R; Sheppard, J; et al. (2004)
When a crystal is subjected to shock compression beyond its Hugoniot Elastic Limit (HEL), the deformation it undergoes is composed of elastic and plastic strain components. In situ time-dependent X-ray diffraction, which allows direct measurement of lattice spacings, can be used to investigate such phenomena. This paper presents recent experimental results of X-ray diffraction from shocked fcc crystals. Comparison is made between experimental data and simulated X-ray diffraction using a post-processor to Molecular Dynamics (MD) simulations of shocked fcc crystals.